Early lateral root formation in response to calcium and nickel shows variation within disjunct populations of Arabidopsis lyrata spp. lyrata. Issue 2 (February 2023) - Veatch-Blohm, Maren E.; Medina, Gustavo; Butler, Jane
Abstract: Root architecture is important in nutrient uptake and avoidance of toxic compounds within the soil. Arabidopsis lyrata spp. lyrata has widespread distribution in disjunct environments that encounter unique stressors starting at germination. Five populations of A. lyrata spp. lyrata show local adaptation to Nickel (Ni) but cross-tolerance to variations in Calcium (Ca) concentration within the soil. Differentiation among the populations begins early in development and appears to impact timing of lateral root formation; therefore the purpose of the study was to understand changes in root architecture and root exploration in response to Ca and Ni within the first three weeks of growth. Lateral root formation was first characterized under one concentration of Ca and Ni. Lateral root formation and tap root length were reduced in all five populations in response to Ni compared to Ca, with the least reduction in the three serpentine populations. When the populations were exposed to a gradient (either Ca or Ni) there were differences in population response based on the nature of the gradient. Start side was the greatest determinant of root exploration and lateral root formation under a Ca gradient, while population was the greatest determinant of root exploration and lateral root formation under a Ni gradient. All populations exhibited about the same frequency of root exploration under a Ca gradient, while the serpentine populations exhibited much higher levels of root exploration under a Ni gradient compared to the two non-serpentine populations. Differences among populations in response to Ca and Ni demonstrate the importance of stress responses early in development, particularly in species that have widespread distribution among disparate habitats.